Intellectual Ethnography of Indonesian Muslims - Syukur, Yanuardi (Buletin Antropologi Indonesia, 2024)
Even though science is considered neutral, the struggle to Islamize science continues to be carried out by Muslim intellectuals. Al Attas is one of the critical intellectuals in this field whose influence has significantly impacted a group of Indonesian Muslim scholars within the INSISTS community. One of the INSISTS figures concerned about the Islamization of knowledge is Hamid Fahmy Zarkasyi. This study attempts to discuss why and how this Islamization was carried out by Indonesian intellectual Muslim. This study uses ethnographic methods in the INSISTS community with literature studies. This research shows that the involvement of Muslim intellectuals in islamization is related to the intention of da’wah, the implementation of the Islamic Worldview, and is made possible by the socio-cultural situation of a democratic Indonesia. The strategy of Islamization of knowledge is carried out by focusing on young intellectual regeneration, writing, and the presence of charisma that supports this vision. Theoretically, this study strengthens Sherry Ortner’s opinion that agency is formed by three components of intention and socio-cultural construction and adds a charisma component as the fourth component that includes agency.